2009
DOI: 10.1159/000216537
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal EEG/Sleep State Analyses: A Complex Phenotype of Developmental Neural Plasticity

Abstract: Computer analyses of EEG/sleep states can be used as physiologic biomarkers of developmental neural plasticity. Frequency- and time-dependent signal processing strategies of cerebral and noncerebral measures can help test current theories of neuronal network maturation in terms of segregation and integration of short-distance versus long-distance neuronal connections throughout the neuroaxis. Specific phenotypic expressions of adaptive or maladaptive neuronal connectivity are proposed based on comparisons of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 283 publications
0
33
1
Order By: Relevance
“…Comparative sleep study results from other authors suggested that the sleep cycle of full term newborns showed ultradian rhythm, with the duration of each cycle lasts about 30-70 minutes, [16] which differed from our observation of the SWC duration, which lasts between 43.0-99.5 minutes. The difference may come from the methodology and defi nition of SWC.…”
Section: Discussioncontrasting
confidence: 99%
“…Comparative sleep study results from other authors suggested that the sleep cycle of full term newborns showed ultradian rhythm, with the duration of each cycle lasts about 30-70 minutes, [16] which differed from our observation of the SWC duration, which lasts between 43.0-99.5 minutes. The difference may come from the methodology and defi nition of SWC.…”
Section: Discussioncontrasting
confidence: 99%
“…60 The FGR children in this study showed an increase in θ power, potentially reflecting alterations in hippocampal and cortical activity, however what this increase means is unclear and deserves further study. Further investigation on early life programming with gene-environment interactions (epigenetics) that influence developmental brain plasticity during critical or sensitive periods of brain and sleep maturation would be imperative to further explore these mechanisms, 61 particularly, as it is known that fetal state behaviors predict adolescent performance later in life. 62 Currently, sleep in childhood is not routinely monitored in children born preterm or FGR.…”
Section: Discussionmentioning
confidence: 99%
“…The study of neonatal sleep is of great importance as it helps determining the degree of maturity of the neonatal brain and can be useful in the assessment of a possible risk of certain disabilities [1][2][3][4]. For example, neonatal sleep was found to be relevant to some syndromes such as sudden infant death syndrome (SIDS) which was found to be related to the immaturity of the respiratory center in the brain.…”
Section: Introductionmentioning
confidence: 99%